Effectiveness of combined antihypertensive treatment depending on the phenomenon of salt sensitivity in patients with refractory arterial hypertension - V V Skibitskiy (Системные гипертензии, 2015)
Purpose of study - evaluate the effectiveness of combined antihypertensive treatmentthat includes direct renin inhibitor in salt-sensitive and salt-resistant patients with refractory hypertension (RHT).Methods and materials. The study included 192 patients with RHT. Based on the results of the V.I.Kharchenko test and a variation of combined antihypertensive therapy, all patients were randomized into groups: group 1 - salt-sensitive patients treated with an ACE inhibitor (ACEI), dihydropyridine calcium antagonist (CA), thiazide diuretic (TD) and direct renin inhibitor aliskiren (subgroup 1A) or b-blocker - BB (subgroup 1B); group 2 - salt-resistant patients treated with ACE inhibitors, dihydropyridine CA, TD and aliskiren (subgroup 2A) or BB (subgroup 2B). In the absence of achieving target BP after 6 weeks from the start of observation, patients started receiving five-component treatment: ACE inhibitor, CA, TD, BB and aliskiren. Initially and after 48 weeks of observation, all patients underwent ambulatory blood pressure monitoring (ABPM).Results. In the group of salt-sensitive patients treatment including aliskiren contributed to achievement of target values of BP in 43.3%, and with pre- scription of BB - in 54.3% of patients. In both groups there was a significant improvement in most of the parameters of ABPM, more pronounced when using BB. Normalization of circadian BP profile was registered significantly more often ( p